Case Report: Syphilitic proximal coronary stenosis with discordant serology: diagnostic validation by optical coherence tomography - Xiong, Jingjie; Gan, Ting; Hu, Jing; Liu, Wenhu; Wang, Xuehua; Li, Han; Lv, Jiaxi; Xiong, Ni; Huang, Yanli; Liu, Qianyi; Yin, Lihui; Wang, Yan; et al. (Frontiers in Medicine, 2025)
Cardiovascular syphilis, a late manifestation of Treponema pallidum infection, remains a diagnostic challenge, particularly when serological tests are discordant. We report a case of a 70-year-old male with recurrent chest tightness and discordant syphilis serology (non-reactive RPR, reactive TPPA). Coronary angiography revealed a critical stenosis at the distal left main coronary artery, specifically involving the ostio-proximal segment of the left anterior descending (LAD) artery. Critically, the absence of systemic atherosclerosis was evidenced by a coronary artery calcium score of zero and normal carotid intima-media thickness. Optical coherence tomography (OCT) provided definitive diagnostic clarity by revealing microstructural features pathognomonic for syphilitic vasculitis: vasa vasorum obliteration, elastic lamina fragmentation, and adventitial fibrosis with microcalcifications. These findings were distinct from atherosclerotic plaque. The patient successfully underwent OCT-guided percutaneous coronary intervention followed by targeted antibiotic therapy. This case highlights the indispensable role of OCT in establishing the etiology of non-atherosclerotic proximal coronary stenosis, underscoring that cardiovascular syphilis must be considered even with non-reactive non-treponemal tests in late-stage disease.